The Costs of Staying Healthy : COVID-19 in LAC - Ballon, Paola (World Bank, Washington, DC, 2021)
COVID-19 closures in Latin American and the Caribbean countries helped to curb the spread of the virus, but inevitably brought negative consequences for households, principally in the form of job losses, income reduction, and, in some cases, food insecurity. Future policy measures should aim to strike the right balance between saving lives and protecting livelihoods. Where closures are necessary, they should be adapted to a country's labor market and other localized conditions so as to minimize profound welfare losses. Governments should strive for robust and agile social safety net systems to be able to respond to the sudden falls in household welfare.